2019
DOI: 10.1159/000502646
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immune Response Involving Multinucleated Giant Hemocytes with Two-Step Genome Amplification in the Drosophilid <b><i>Zaprionus indianus</i></b>

Abstract: Previously, a novel cell type, the multinucleated giant hemocyte (MGH) was identified in the ananassae subgroup of Drosophilidae. These cells share several features with mammalian multinucleated giant cells, a syncytium of macrophages formed during granulomatous inflammation. We were able to show that MGHs also differentiate in Zaprionus indianus, an invasive species belonging to the vittiger subgroup of the family, highly resistant to a large number of parasitoid wasp species. We have classified the MGHs of Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(35 citation statements)
references
References 38 publications
(58 reference statements)
2
33
0
Order By: Relevance
“…Similar to our previous observations in Z. indianus [ 13 ], we found an MDBS in D. ananassae MGHs, which appeared to contribute to the formation of an electron-dense layer along the attachment site with the parasitoid. The well-organized, lamellar structure of this electron-dense layer likely facilitates strong and stable attachment of MGHs to parasitoids, encapsulation, and possibly degradation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to our previous observations in Z. indianus [ 13 ], we found an MDBS in D. ananassae MGHs, which appeared to contribute to the formation of an electron-dense layer along the attachment site with the parasitoid. The well-organized, lamellar structure of this electron-dense layer likely facilitates strong and stable attachment of MGHs to parasitoids, encapsulation, and possibly degradation.…”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, these elongated cells fuse with each other and form the terminally differentiated MGHs, which have the capacity to encapsulate invaders [ 12 ]. Previously, in Z. indianus , we found that MGHs carry relatively few vesicles and possess a sponge-like overall ultrastructure formed by an irregular cytoplasmic canalicular system [ 13 ]. By contrast, our current analysis of D. ananassae MGHs revealed a large number of diverse vesicular systems and a canalicular organization which is mostly localized at the cell periphery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last article published in this issue Gyöngyi Cinege and colleagues carried out functional and developmental analysis of hemocyte subsets and immune compartments. To this end, the authors examined cellular immune re-sponses involving multinucleated giant hemocytes from Zaprionus indianus, an Afrotropical drosophilid species [13]. The authors concluded that the unique features of the cell-mediated immunity of this species provides clues towards the understanding of the immune response accomplished by multinucleated giant hemocytes.…”
mentioning
confidence: 99%